STRATEGI PENGEMBANGAN USAHA AYAM PEDAGING (BROILER) DENGAN SISTEM KEMITRAAN DAN SEWA KANDANG - Agustina, widyasworo; moeis, edya moelia (AVES: Jurnal Ilmu Peternakan, 2024)
This research was conducted at one of the farms of PT. Dinamika Megatama Citra (DMC), located in Selokajang Village, Srengat District, Blitar Regency, with a broiler chicken population of 1,800. The study aimed to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats) to develop strategies for broiler chicken business growth in the village. This analysis is crucial as a foundation for business sustainability, particularly after the Covid-19 pandemic, which significantly impacted the economy and led to many broiler chicken houses becoming unused despite being in good condition. The study revealed that, in a single production cycle, the total live weight of the chickens reached 3,862 kilograms, sold at IDR 20,476 per kilogram, resulting in total sales revenue of IDR 79,006,425. Additional income from selling used cartons and sacks amounted to IDR 219,000, bringing the total revenue to IDR 79,295,425. Fixed costs incurred were IDR 1,487,200, and variable costs amounted to IDR 69,282,000, resulting in a total production cost of IDR 70,758,200. Thus, the profit earned per production cycle was IDR 8,539,225. The Return Cost Ratio (RCR) of 1.12 indicates that every IDR 1 invested in this business generates revenue of IDR 1.12, with a profit margin of IDR 0.112. Based on a SWOT analysis, the proposed development strategies for the broiler chicken business include partnership models and cage rental systems. According to the Internal-External (IE) Matrix, the broiler business with partnership and cage rental systems is positioned in Cell I, indicating a condition of growth and development with a strong position and high attractiveness.